2019
DOI: 10.1016/j.avb.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of intimate partner violence victimisation: An inclusive review across gender and sexuality

Abstract: Do w nlo a d e d fro m: h t t p://i n si g h t. c u m b ri a. a c. u k/i d/ e p ri n t/ 4 5 2 7/ U s a g e o f a n y i t e m s f r o m t h e U n i v e r s i t y o f C u m b r i a' s i n s t i t u t i o n a l r e p o s i t o r y 'I n s i g h t' m u s t c o n f o r m t o t h e f o l l o w i n g f a i r u s a g e g u i d e l i n e s .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 115 publications
4
94
0
2
Order By: Relevance
“…In contrast to other psychiatric disorders, there are inherent sex biases related to trauma exposure type and the pathophysiology of PTSD. For example, females tend to be overrepresented in civilian cases of PTSD as a result of intimate partner violence and/or rape [Laskey et al, 2019], whereas males are significantly overrepresented in studies of combatexposed PTSD [Lehavot et al, 2018]. Still, a US epidemiology study of PTSD revealed significantly higher prevalence in past-year and lifetime PTSD in female versus male veterans (past year: 11.7% vs. 6.7%; lifetime: 13.4% vs. 7.7%) and civilians (past year: 6% vs. 2.6%; lifetime: 8% vs. 3.4%) [Lehavot et al, 2018].…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…In contrast to other psychiatric disorders, there are inherent sex biases related to trauma exposure type and the pathophysiology of PTSD. For example, females tend to be overrepresented in civilian cases of PTSD as a result of intimate partner violence and/or rape [Laskey et al, 2019], whereas males are significantly overrepresented in studies of combatexposed PTSD [Lehavot et al, 2018]. Still, a US epidemiology study of PTSD revealed significantly higher prevalence in past-year and lifetime PTSD in female versus male veterans (past year: 11.7% vs. 6.7%; lifetime: 13.4% vs. 7.7%) and civilians (past year: 6% vs. 2.6%; lifetime: 8% vs. 3.4%) [Lehavot et al, 2018].…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…Men have also stressed that they feel inclined to stay with abusive partners to remain with and protect their children (Bates, 2019c), as, again, there is little provision available which allows them to remove both themselves and their children away from abusive settings (Mankind Initiative, 2020). Studies also demonstrate that stigma is experienced by men reporting same-sex DVA (Calton, Cattaneo, & Gebhard, 2016;Laskey, Bates, & Taylor, 2019), which is represented in their negative experiences of help-seeking (Donovan & Barnes, 2019), including reporting to law enforcement (Finneran & Stephenson, 2013), and the difficulty they face in accessing services (Stiles-Shields & Carroll, 2015). Taken together, such studies explain why men report that being recognised as victims is of the utmost importance to them in their help-seeking EXPERIENCES SUPPORTING MALE VICTIMS OF DOMESTIC ABUSE 7 journeys, and is the foundation on which all other help, support and access can be achieved (Wallace, Wallace, Kenkre, Brayford, & Borja, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Further scholarship should continue to draw on victims' experiences, and broadly consider the needs of a diverse group of survivors of different types of abuse. Although this study focused on women, as Laskey et al (2019) have suggested, future work should attend more carefully to male survivors and those from the LGBTQ+ community to avoid marginalizing those groups of IPV survivors. Following the work of Storer et al (2018), future research should take into account phenomenological narratives from survivors and provide recommendations for the application of those findings directly to clinical and advocacy practice.…”
Section: Resultsmentioning
confidence: 99%